IMPROVING HEALTHY BEHAVIOR IN YOUTH TO PREVENT HYPERTENSION - Minarti Minarti; Siti Nur Kholifah; Dwi Ananto Wibrata Wibrata; Ach. Arfan Adinata (Health Community Engagement, 2022)
The health cadre group at the junior high school level is a group of early adolescents who have psychological characteristics in the form of anxiety, conflict, imagining, group activities and the desire to try something new, so that this group of early adolescents can receive correct information so that they can increase efforts to behave in a healthy life. This teenager has high curiosity, then explores everything and tries everything he has never received, especially the prevention of hypertension. The purpose of this community service is to improve the healthy life behavior of school health cadres as an effort to prevent hypertension. The method used is training with a target of 50 students of school health cadres in East Surabaya Junior High School. Based on the results of the pre-test and post-test assessments, it is known that almost all health cadres (98%) have increased scores, and 2% have fixed scores. The difference between the post-test and pre-test results ranged from 0-34 points. The skills of school health cadres were assessed through assignments to identify the healthy behavior of those closest to them, the results showed that more than 76% of someone identified as having a habit of eating a balanced diet consisting of carbohydrates, vegetables, fruit and side dishes, getting enough rest as much as 70%, but also getting 60 % of their families smoke in the house, play a lot with gadgets by 54% and if there are problems, they are discussed with parents by 68%. Empowerment carried out through health cadres is one way to anticipate the increase in hypertension in adolescents.